The possible meanings of care: self-care and care-for-the-other - Fábio Solon Tajra; Ricardo José Soares Pontes; Francisco Herlânio Costa Carvalho (Universidad de Antioquia, 2017)
Objective. To understand and to reflect about care based on the experiences of managers, professionals and users of maternal and child health services. Methods. We developed an evaluative research with a qualitative approach in a Northeastern state of Brazil with extensive experience in the regionalization and implementation process of integrated health networks. Semi-structured interviews were carried out with 68 subjects and direct observation of the maternal and child health services. We adopted the theoretical reference framework of Gadamer's hermeneutics to analyze the narratives. Results. Some units of meaning were present, such as: perception and knowledge about oneself; exercise of autonomy; weaknesses in the provision of resources for the materialization of self-care; and difficulties in accessing health services and care practices. We perceive that care is dynamic, comprises various subjective aspects with respect to the singularities of the subjects and is related to the possibility of generating both individual and collective transformation. Conclusion. Care is built based on a movement among the subjects and between them and the social and health services. Thus, when we intend to take care, we need to consider this instead of focusing care solely on the technical support of health professionals.   How to cite this article: Tajra FS, Pontes RJS, Carvalho FHC. The possible meanings of care: self-care and care-for-the-other. Invest. Educ. Enferm. 2017; 35(2): 199-209.